Thermal decomposition of n-hexane in organic Rankine cycle: a study combined ReaxFF reactive molecular dynamic and density functional theory - Liu, Wei; Wang, Nan; Chen, Jun; Shen, Aijing; Yan, Fei (Frontiers in Energy Research, 2023)
The thermal decomposition mechanism of n-hexane is investigated by using density functional theory and ReaxFF force field. The initial decomposition reactions, the effect of temperature on thermal decomposition and first-order kinetics are analyzed. The results show that the C-C bonds in n-hexane molecule are more easily decomposed than that of C-H bonds, and the breakage of C3-C4 bond is the main initial decomposition reaction. The main decomposition products of n-hexane are H2, CH4, C2H2, C2H4, C2H6, and C3H6. The decomposition rate of n-hexane is accelerated by temperature. The apparent activation energy and pre-exponential factor of n-hexane thermal decomposition are 209.8 kJ mol−1 and 1.1 × 1013 s−1, respectively.